COMPARISON OF SUITABLE EXTRACTANTS USED IN SOIL PHOSPHORUS TESTING ON DIFFERENT SOILS - S. U. Khan; T. H. Flower; Q. U. Khan; A. A. Khakwanı; O. U. Sayal; I. Bakhsh (Journal of Animal and Plant Sciences, 2018)
The present study was carried out to compare the six Phosphate extractants applied on fourteen different soil types. The extractants used include Acetic acid, Sodium acetate buffer (Morgan solution), Ammonium acetate buffer (Modified Morgan’s solution), Sodium bicarbonate (Olsen extractant), Acidified ammonium fluoride (Bray – I reagent) and Anion Exchange Resin (AER). The fourteen soil were different in soil properties as pH, Organic matter content, Fe, Al and soil texture. The soil were grouped in to two on the basis of pH (acidic and alkaline). The results showed that Phosphate extracted by various extractant showed significant difference at 1% level of probability. The highest Phosphate concentration was measured in different soil by using the Bray I extractant. The lowest was determined in AER. Significant correlations have been found between the extractant except for Bray which showed non – significant correlation. Comparing the effectiveness of soil pH showed positive correlation between the extractants at pH range of 5.2 to 6.3. While at higher pH in range of 6.3 to 7.9 was non – significant. It may be concluded from the result that Bray I was effective in extracting P concentration from soil in acidic condition while Acetic acid and Sodium Bicarbonate (Olse reagent) were more effective under slightly acidic to alkaline condition.
Keywords: Soil; Phosphate; Extractants; Alkaline soils; Acidic soils; correlations